Effects of lockdown on acute coronary syndrome incidence in an area without community transmission of COVID-19. Issue 1 (21st June 2021) - Ferreira, David; Graffen, Simon; Watkins, Brendan; Peters, Bridie; Lim, Geok Jim; Kamalanathan, Harish; Leitch, James; Sverdlov, Aaron; Collins, Nicholas; Boyle, Andrew; Davies, Allan
Abstract : Objective: To assess the changes in cardiac hospitalisations, acute coronary syndromes (ACS) and out-of-hospital cardiac arrest (OOHCA) during COVID-19 isolation compared with prior time periods in an area of low COVID-19 disease incidence. Methods: Review of all cardiology admissions, non-ST segment elevation myocardial infarction (NSTEMI), ST-segment elevation myocardial infarction (STEMI) requiring urgent catheter laboratory activation and OOHCA. The 10-week period of government-imposed social isolation (23 March–31 May 2020) was compared with the same period in 2018, 2019 and a 10-week period prior to social isolation (6 January–15 March 2020). Incidence rate ratios were calculated. Symptom to balloon time was also compared for those requiring catheterisation laboratory activation for STEMI. Results: The incidence of COVID-19 in the health district was 0.14 per 100 000 per day during the isolation period. There was a significant reduction in cardiology hospitalisations, NSTEMI and STEMI presentations without changes in OOHCA or symptom to balloon time for STEMI. Conclusions: We observed a significant decline in cardiology presentations during social isolation without widespread COVID-19 disease. This provides further evidence for the important influence of social and behavioural factors on coronary event rates.